Aspek Hukum Konsolidasi Tanah Perkotaan di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The character of substantive ULC Law has not vet been adequate to protect the implementor and ULC participants. From side of ULC participants, the weakness of legal character of ULC derives from obscurity of ULC regulations to determine definitions and scope of ULC Program. From side of ULC implementor, voluntary method used by Regulation of the Head of National Land Agency Number 4 of 1991 on Land Consolidation (RHNLA 4191) cannot reply the constraint of continuity of ULC because irrational individual egoism from some of land owner in ULC location which did not gave their approval or terminated agreement unilaterally. These suggesstiottv could he done. First, the National Land Agency (NLA) must strictly continue the ULC program, even though the ownership of the land still belongs to the dissenting landowners. Second, creating legal norm that regulate the minority of the dissenting landowners must obey the agreement of the majority of agreed ULC participants.. Third, to apply the compulsory acquisition of land over the dissenting landowners in ULC location